A Theoretical study on the charge and discharge states of Na‐ion battery cathode material, Na1+xFePO4F. Issue 1 (20th October 2018) - Shinagawa, Chikashi; Morikawa, Yusuke; Nishimura, Shin‐ichi; Ushiyama, Hiroshi; Yamada, Atsuo; Yamashita, Koichi
Abstract : Na2 FePO4 F is a promising cathode material for a Na‐ion battery because of its high electronic capacity and good cycle performance. In this work, first principle calculations combined with cluster expansion and the Monte Carlo method have been applied to analyze the charge and discharge processes of Na2 FePO4 F by examining the voltage curve and the phase diagram. As a result of the density functional theory calculation and experimental verification with structural analysis, we found that the most stable structure of Na1.5 FePO4 F has the P 21 / b 11 space group, which has not been reported to date. The estimated voltage curve has two clear plateaus caused by the two‐phase structure composed of P 21 / b 11 Na1.5 FePO4 F and Pbcn Na2 FePO4 F or Na1 FePO4 F and separated along the c ‐axis direction. The phase diagram shows the stability of the phase‐separated structure. Considering that Na2 FePO4 F has diffusion paths in the a ‐ and c ‐axis directions, Na2 FePO4 F has both innerphase and interphase diffusion paths. We suggest that the stable two‐phase structure and the diffusion paths to both the innerphase and interphases are a key for the very clear plateau. We challenge to simulate a nonequilibrium state at high rate discharge with high temperature by introducing a coordinate‐dependent chemical potential. The simulation shows agreement with the experimental discharge curve on the disappearance of the two plateaus. © 2018 Wiley Periodicals, Inc. Abstract : Na + can diffuse through both inner‐ and interphase diffusion paths at a moderate rate.